Comparative Determination of Chlorpromazine in Pharmaceutical Injectable Veterinary and Human Formulations by Spectrophotometric and High Performance Liquid Chromatographic Methods - Fouad K. Mohammad; Lubna A. Kafi; Nabaa K. Al-Hayani; Fereal M. Mahdi; Ahmed J. Essa (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Chlorpromazine (CPZ) is a phenothiazine tranquilizer used in humans and animals. Rapid determinationof the drug in pharmaceutical preparations is often needed. The aim of the study was to further examine and ascertainasimple spectrophotometric method in comparison with a high performance liquid chromatographic (HPLC) methodfor the determination of CPZ concentrations in injectable pharmaceutical formulations used in man and animals.Methods: Concentrations of CPZ in injectable pharmaceutical formulations for human and veterinary uses weredetermined by a modified spectrophotometric method and by an HPLC method with appropriate standard calibrationcurves. The spectrophotometric method of CPZ determinationwas conducted by diluting 0.1 ml of the veterinary(5%) or 0.3 ml of human (0.5%) formulations to 200 ml of 0.1N sulfuric acid. Four ml of the diluted CPZ samples orthe standard solutions were mixed with 2 ml of 50% sulfuric acid. Then an aliquot of 0.2 ml of 2% ferric nitrate wasadded to the mixture. After 15 minutes, the absorbance was measured at 530 nm against water and vehicle blanksusing a spectrophotometer. The HPLC method applied in the present study consisted of reversed phase gradientchromatography with a C18 column and the eluent was (A) 50 mmol NaH2PO4, pH 2.5 and (B) acetonitrile - 50mmol NaH2PO4, pH 2.5 (60:40 v/v), flow rate at 1 ml/min, with a gradient of 15-55% B in 10 min, to 100% B in20 min, and 280-nm UV detection. From the calibration curves of CPZ standards, the following were calculated:Limit of detection limit (LOD) = 3.3 x SD/slope; Limit of quantitation (LOQ) = 10 x SD/slope, where SD is thestandard deviation of response of CPZ concentrations of the calibration curves.Linear regression analysis and relatedcoefficients of correlations were applied on the calibration curves. Results: The calibration curves of CPZ againstwater or vehicle blanks as determined by the spectrophotometric method or by the HPLC method were linear withstrong correlations (r = and / or >0.99). Based on the calibration curves, limit of detection and limit of quantitation thespectrophotometric method were comparable to those of the HPLC one. The contents CPZ in human and veterinaryinjectable formulations as determined by the spectrophotometricmethod were in accordance (100.6% and 102%,respectively)to the concentrations claimed on the labels of the formulations.Conclusion: The present results introduce a simple spectrophotometric method that could be used for routinemeasurement of CPZ concentrations in pharmaceutical formulations, with the added benefits of linearity, precisionand cost effectiveness.